FETAL OMPHALOCOELE SONOGRAPHIC DIAGNOSIS - Nayab Alia; Waseem Shahzad (Journal of University Medical & Dental College, 1970)
ABSTRACT Congenital anomalies affect approximately 2 to 3% of all live births every year.1 Sonographic antenatal detection of anomalies has become a new goal of modern obstetrics management. We report a case of omphalocole with associated anomalies, its sonographic detail and clinical implications, managed at our institution.